GERMPLASM COLLECTION OF A GARDEN PEA (PISUM SATIVUM L.) AND ITS APPLICATION IN RESEARCHES - A. A. Sinjushin; O. A. Ash; G. A. Khartina (Труды по прикладной ботанике, генетике и селекции)
In this paper we provide characteristics of the germplasm collection of cultivars, mutants, marker lines and recombinants of the garden pea (Pisum sativum L.) stored at the Genetics Dept. of Biological Faculty of the Lomonosov Moscow State University. A history of this collection is briefly described together with the main scopes of its application in both retrospectives and perspectives.